Mobbing in Health Professionals: A Study in A Public Hospital - Taşkın Kılıç; Fatma Çiftçi; Şeyma Şener (Association of Nurse Managers, 2016)
INTRODUCTION: Mobbing has been indicated to have psychological and physical effects on employees, and it has been the subject of investigations performed in many different sectors. This study was performed with the intention to determine correlations (if any) between local workers (native inhabitants of the concerned province), and foregn workers (those coming from another province) employed in a state hospital situated in the Black Sea Region with respect to exposure to mobbing, and also between mobbing,and some demographic variables. METHODS: A survey employed to gather data from the health organizations staff in Public Hospital included; doctors, nurses and other health staff members. Interviews were used and questionnaires were distributed to the hospitals with a final sample of 160 respondents. Statistical analysis of the data were conducted with the use and in the statistical environments of the SPSS software-package. RESULTS: As an outcome of the study, mobbing behaviour of employees differed significantly according to the city they come from (native inhabitants, and foreigners). Also, workers from other provinces are exposed to mobbing more frequently than the native ones. In addition, other demographic characteristics of mobbing behaviours differ significantly. DISCUSSION AND CONCLUSION: It was concluded that exposure to mobbing behaviours differed according to the age, title, and educational status of the employees, but a significant difference was not found as for exposure to mobbing behaviour regarding the marital status and experience of the health care workers.